Cost-of-illness analysis reveals potential healthcare savings with reductions in type 2 diabetes and cardiovascular disease following recommended intakes of dietary fiber in Canada - Abdullah, Mohammad M. H.; Gyles, Collin L.; Marinangeli, Christopher P. F.; Carlberg, Jared G.; Jones, Peter J. H. (Frontiers in Pharmacology, 2015)
Background: Type 2 diabetes (T2D) and cardiovascular disease (CVD) are leading causes of mortality and two of the most costly diet-related ailments worldwide. Consumption of fiber-rich diets has been repeatedly associated with favorable impacts on these co-epidemics, however, the healthcare cost-related economic value of altered dietary fiber intakes remains poorly understood. In this study, we estimated the annual cost savings accruing to the Canadian healthcare system in association with reductions in T2D and CVD rates, separately, following increased intakes of dietary fiber by adults. Methods: A three-step cost-of-illness analysis was conducted to identify the percentage of individuals expected to consume fiber-rich diets in Canada, estimate increased fiber intakes in relation to T2D and CVD reduction rates, and independently assess the potential annual savings in healthcare costs associated with the reductions in rates of these two epidemics. The economic model employed a sensitivity analysis of four scenarios (universal, optimistic, pessimistic, and very pessimistic) to cover a range of assumptions within each step. Results: Non-trivial healthcare and related savings of CAD$35.9-$718.8 million in T2D costs and CAD$64.8 million–$1.3 billion in CVD costs were calculated under a scenario where cereal fiber was used to increase current intakes of dietary fiber to the recommended levels of 38 g per day for men and 25 g per day for women. Each 1 g per day increase in fiber consumption resulted in annual CAD$2.6 to $51.1 million savings for T2D and $4.6 to $92.1 million savings for CVD. Conclusion: Findings of this analysis shed light on the economic value of optimal dietary fiber intakes. Strategies to increase consumers’ general knowledge of the recommended intakes of dietary fiber, as part of healthy diet, and to facilitate stakeholder synergy are warranted to enable better management of healthcare and related costs associated with T2D and CVD in Canada.